Arah Pengelolaan Jurnal Ilmiah Kelas Menulis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung - Fitriani Fitriani; Hidayatul Fikra; Susanti Vera; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2024)
This research aims to discuss the management of scientific journals. This research uses a qualitative approach by applying descriptive-analytical methods. The results and discussion show that journal managers deserve appreciation for their dedication to improving the performance of scientific publications in the world of higher education. This research concludes that higher education alumni who continue to dedicate themselves to managing scientific journals are certain to have sufficient capacity to accelerate scientific publications if they have the opportunity to be appointed as lecturers. Because future lecturers need adequate mastery in the field of scientific publications.